Characteristics of Refuse-Derived Fuel (RDF) at The Waste Processing Facility (WPF) of The Faculty of Engineering, Untirta - Suhendi, Endang; Heriyanto, Heri; Jundika, Paerus; Rizkiantika, Natasya (Chemical Engineering Department, Engineering Faculty, Universitas Sultan Ageng Tirtayasa, 2023)
Landfill in Cilegon City has an impact on the environment, so processing is needed, one of which is converting waste into RDF fuel. The conversion of waste into RDF provides benefits by reducing the amount of waste sent to landfills and utilizing renewable energy as fuel. The composition of mixed materials in RDF has potential characteristics that affect the quality of the resulting RDF. The study objective is to study the effect of the composition of a mixture waste of organic (leaves) and LDPE plastic on the characteristics of RDF. The research was conducted with composition ratios of organic waste (leaves) and LDPE plastic waste at 95:5, 90:10, 85:15, and 80:20 (% wt.). The results showed that the optimal RDF product was produced with a composition of 85:15 and with the addition of 10% starch. These results indicate the characteristics of RDF, including an ash content of 14.681%, moisture content of 11.215%, volatile matter of 54.465%, fixed carbon of 19.469%, calorific value of 4598.017%, bulk density of 0.706 g/cm3, and compressive strength of 6.69 kg/cm2. It has the potential to be a good alternative for using RDF as fuel in boilers.